Biological and Chemical Diversity of Ascidian-Associated Microorganisms - Lei Chen; Jin-Shuang Hu; Jia-Lei Xu; Chang-Lun Shao; Guang-Yu Wang (Marine Drugs, 2018)
Ascidians are a class of sessile filter-feeding invertebrates, that provide unique and fertile niches harboring various microorganisms, such as bacteria, actinobacteria, cyanobacteria and fungi. Over 1000 natural products, including alkaloids, cyclic peptides, and polyketides, have been isolated from them, which display diverse properties, such as antibacterial, antifungal, antitumor, and anti-inflammatory activities. Strikingly, direct evidence has confirmed that ~8% of natural products from ascidians are actually produced by symbiotic microorganisms. In this review, we present 150 natural products from microorganisms associated with ascidians that have been reported up to 2017.